'Wax bloom' on beeswax cultural heritage objects: Exploring the causes of the phenomenon. (27th April 2015) - Bartl, B.; Kobera, L.; Drábková, K.; Ďurovič, M.; Brus, J.
<x xml:space="preserve">Abstract</x> The term 'wax bloom' is used to describe a thin whitish crystalline layer that develops on the surface of beeswax objects under specific conditions. This phenomenon is undesirable, especially in the cases of objects with aesthetic or informational value, such as wax sculptures or historical seals. A combination of solid‐state NMR and FTIR measurements allowed to obtain fairly detailed insight into the problem and to suggest a probable mechanism of its development. Secondary crystallization of unsaturated hydrocarbons from beeswax was determined as a primary cause. After the macroscopic solidification of beeswax from the melt, these molecules remain for months in a highly mobile, liquid‐like state. This facilitates their diffusion to the surface, where they eventually crystallize, forming the 'wax bloom' effect. Although these results are of particular interest with respect to the conservation of beeswax artifacts, they are relevant to this material in general and help with understanding its unique properties. Copyright © 2015 John Wiley & Sons, Ltd.